The Importance of Training Need Assessment on Competency-Based Training of Technical Guidance of Energy Auditor in Cement Industry - Sunyoto Sunyoto; Robinson Situmorang; Etin Solihatin (STKIP Singkawang, 2020)
Training needs assessment or training needs analysis is a move made prior to training and a part in the design of integrated training in order to obtain a comprehensive picture of the material, the allocation of time, and learning strategies that should be applied in conducting Technical Guidance Training of Energy Auditor. In this case, identifying training needs (Training Needs Analysis) is the second step after identify desired result (SKKNI Comply) in the development of a training model Technical Guidance of energy Auditor. Identification of training needs carried out by the training institutions in the cement industry is micro case, namely the identification process to find out the